2004
DOI: 10.3390/s40670105
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Characterization of a Thiol SAM on Gold as a First Step for the Fabrication of Immunosensors based on a Quartz Crystal Microbalance

Abstract: Abstract:In order to develop a robust biosensor based on quartz crystal microbalance technique for antigen detection, a control of the steps of the surface functionalization has been performed by impedance spectroscopy. The gold electrode is functionalized with the self-assembled monolayer technique. The high insulating properties of the acidic thiol monolayer has been characterized with cyclic voltammetry and impedance spectroscopy. The modified surface is activated with N-hydroxysuccinimide(NHS) and 1-(3-(di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 6 publications
3
54
0
Order By: Relevance
“…is is assigned functionalized GNPs (mean diameter = 27.3 nm, polydispersity index to the vibration mode of alkyl thiol chains. Bands at 1125-1335 cm -1 are assigned to the N-C stretch [31]. ese results con rm the presence of covalent thiol and amine bonds found in our PEI stabilized choline-GNPs.…”
Section: Nanoparticle Characterizationsupporting
confidence: 65%
“…is is assigned functionalized GNPs (mean diameter = 27.3 nm, polydispersity index to the vibration mode of alkyl thiol chains. Bands at 1125-1335 cm -1 are assigned to the N-C stretch [31]. ese results con rm the presence of covalent thiol and amine bonds found in our PEI stabilized choline-GNPs.…”
Section: Nanoparticle Characterizationsupporting
confidence: 65%
“…[7] The presence of the large band in the range of 500 to 750 cm -1 illustrates the formation of a covalent gold-sulfur bond. [8] The ESD result (Fig.2B) also shows that the particle contained Fe, O, C and S elements. Fig.…”
Section: Characterizationmentioning
confidence: 98%
“…It is easy to denote the presence of the SAM, for instance, on gold electrode since it can be oxidized to form gold oxides which are reduced to metallic gold again. A fresh gold electrode was evaluated before and after thiol deposition by means of a triangular potential scanning (Tlili et al, 2004) and it was observed that the oxidation reaction was reduced and no cathodic current peak was observed after the SAM formation of thiol. The stability of oquinone produced on glassy carbon electrode modified with single-walled carbon nanotubes was confirmed by CV (Panini et al, 2008).…”
Section: Cyclic Voltammetrymentioning
confidence: 99%
“…The magnetic force was useful to enhance the response of the sensor. Many other studies were developed using the QMC technique to confirm the deposition of biological molecules on self-assembled superstructures and immunosensor assay (Shen et al, 2001;Calvo et al, 2004;Tlili et al, 2004;Mutlu et al, 2008;Boujday et al, 2009). A deep discussion on the use of QMC technique on the step-by-step immunosensor characterization and on immunosensor assay can be found in another specific chapter in this book.…”
Section: Other Electrochemical Techniquesmentioning
confidence: 99%